ANALYSIS OF THE EXPERIENCE OF CONSTRUCTING AND IMPLEMENTING DIDACTIC MODELS OF THE COURSE "GENERAL PSYCHOLOGY" IN INSTITUTIONS OF HIGHER EDUCATION OF UKRAINE - Semychenko, Valentyna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article deals with the problem of designing didactic models of training courses included in the training plans of future psychologist students. The purpose of the research is to critically analyze the experience of designing the content and structure on the example of the "General Psychology" course in higher educational institutions of Ukraine. The task of the research: to determine the initial theoretical positions regarding the specifics and features of teaching the "General Psychology" course; to analyze the content of work programs on the subject "General Psychology", which is taught in a number of higher educational institutions of Ukraine; compare the logic of determining the structure of the course (basic topics, the order of their presentation in the content of the programs); carry out a critical analysis of relevant theoretical models, summarize the experience of designing a relevant didactic model; determine the optimal structure of the course. Research methods: 1) theoretical: analysis, synthesis, consideration of the inductive or deductive method of presentation of educational material, comparison, theoretical generalization; 2) pedagogical observations, analysis of students’ activities in the process of studying the relevant subject, assessment of learning results. As a result of the study, the specifics of the subject "General Psychology", its role in the professional training of future students, tasks performed in the study process were revealed. Didactic models developed and implemented in a number of higher education institutions of Ukraine, as well as reflected in a number of textbooks, were analyzed. Typical features of their design are revealed. Based on the critical analysis, three main design strategies were identified: inductive, deductive and mixed. The expediency of constructing the content of the educational subject "General Psychology" on an inductive basis is argued. Based on the results of the analysis, the normative content and structure of the "General Psychology" course was determined, the effectiveness of which was confirmed in the process of teaching this discipline in the process of professional training of future psychologists.